2007
DOI: 10.1158/0008-5472.can-07-2536
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Profiling of Basal and Luminal Breast Cancers

Abstract: Basal and luminal are two molecular subtypes of breast cancer with opposite histoclinical features. We report a combined, high-resolution analysis of genome copy number and gene expression in primary basal and luminal breast cancers. First, we identified and compared genomic alterations in 45 basal and 48 luminal tumors by using 244K oligonucleotide array comparative genomic hybridization (aCGH). We found various genome gains and losses and rare high-level gene amplifications that may provide therapeutic targe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
291
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 259 publications
(324 citation statements)
references
References 50 publications
26
291
2
1
Order By: Relevance
“…Data generated with this platform not only provided a detailed characterisation of the genomic profiles of these cell lines, but also allowed for a direct integration of genomic and transcriptomic data. Our results demonstrate that breast cancer cell lines have genomic and transcriptomic features that recapitulate those of primary breast cancers [2, 4,34,35,45]. First, in accordance with previous studies [1, 4], we show that breast cancer cell lines can be subclassified in basal-like and luminal subgroups and that the genes associated with each subgroup are remarkably similar to those significantly expressed in primary basal-like and luminal breast cancers, respectively [3,5,6].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Data generated with this platform not only provided a detailed characterisation of the genomic profiles of these cell lines, but also allowed for a direct integration of genomic and transcriptomic data. Our results demonstrate that breast cancer cell lines have genomic and transcriptomic features that recapitulate those of primary breast cancers [2, 4,34,35,45]. First, in accordance with previous studies [1, 4], we show that breast cancer cell lines can be subclassified in basal-like and luminal subgroups and that the genes associated with each subgroup are remarkably similar to those significantly expressed in primary basal-like and luminal breast cancers, respectively [3,5,6].…”
Section: Discussionsupporting
confidence: 90%
“…By correlating the awssmoothed log2 aCGH ratios (copy number states) with expression levels using Pearson's correlation, we identified 753 genes whose expression significantly positively correlates with copy number changes (adjusted P-value \0.05, Table 3; Supplementary Table S5). This gene list generated by this analysis was enriched for genes mapping to chromosomes 17 (10.36%), 8 (9.69%), 11 (9.56%), 1 (9.03%), 3 (7.57%) and 6 (7.04%), and, as expected, one of the genes that displayed the strongest correlation was ERBB2 (HER2) 4,34,35]. Furthermore, genes whose expression levels correlate with copy number and are amplified in breast cancer cell lines could be identified in a systematic fashion.…”
Section: Identification Of Genes Whose Expression Correlates With Copmentioning
confidence: 55%
“…Nevertheless, IGF1R may have some relevance in a subgroup of aggressive basal/triple-negative tumors. 2,37,38 It is noteworthy that in this study, phenotypes have been only stratified according to immunohistochemical and in situ hybridization (for HER2 tumors) results. In addition, besides the HR-positive status, Bcl2, p53 and Ki67 data were taken into consideration for classifying tumors into luminal A or luminal B, based on the important role of apoptosis and proliferation-related genes emphasized in previous studies, [39][40][41] and also supported by our study.…”
Section: Discussionmentioning
confidence: 99%
“…Adélaïde et al [33] observed rare high-level amplifications in basal tumors affecting small regions, including PIK3CA (3q26), IGF1R (15q26), and CCNE1 (19q11-12), but also single genes, such as EGFR (7p11), FGFR2 (10q26), and BCL2L2 (14q11). EGFR, FGFR2, and IGF1R are tyrosine kinase receptors with a broad mitogenic and angiogenesis function and thus can serve as potential therapeutic targets.…”
Section: Genomic Profiling Of Blbcmentioning
confidence: 99%
“…In the same line, specific genomic losses were also detected in basal subtype. The loss of heterozygosity (LOH) at 4p and 5q has been able to define a subclass of BLBC [33,34]. Losses of 4p and 5q associated with BLBC targeted several genes including candidate or known tumor suppressing genes such as SLIT2 (4p15.31), GPR125 (4p15.31), RASA1 (5q14.3), and APC (5q22.2) [33].…”
Section: Genomic Profiling Of Blbcmentioning
confidence: 99%